Estudo da viabilidade de equipamento LIBS-LIF contínuo para aumento do limite de detecção do mercúrio - Souza, Daniele de (2017)
This work aims to verify the feasibility of a continuous LIBS-LIF equipment construction at 405 nm for heavy metals analysis, focusing on mercury. We have studied experimentally a diode laser of a continuous light source (377 nm), which interferes in the process of formation and development of the plasma. The evolution of the temperature, electron density, scattering and increase of the spectral intensities were analyzed, but no alteration was observed. Qualitative explanations for the absence of interference and the benefits of this system were presented. Pumping rate considering a two-level atomic system was qualitatively analyzed. Preliminary results showed that continuous LIBS-LIF system is able to increase sensitivity by up to 2 orders of magnitude over pulsed LIBS-LIF. Absence of interference in plasma evolution allows the use of the same wavelength for the excitation and measurement, which is not feasible in the current pulsed systems.